How literacy resources contribute to a gender inclusive classroom (Kairaranga, 2022)
The New Zealand Curriculum requires schools to be inclusive of all areas of diversity, highlighting the need for schools to ensure children of all genders feel physically and emotionally safe. Children develop concepts and expectations of gender norms at school which can influence self-esteem. Gender-inclusive classrooms are a safe environment for children to explore and express gender identities. One way that gender-inclusive classrooms can be achieved is through children’s literature, which can result in less bullying at school and higher self-esteem in gender-diverse children. The research question for this study is: what are New Zealand primary school teachers’ understandings of how literacy resources contribute to gender-inclusive classrooms? Semi-structured interviews were used to gather qualitative data to answer this question. Data were analysed through a thematic approach and revealed a need for professional development for primary school teachers in Aotearoa to confidently incorporate gender-inclusive and queer literacy resources for a gender-inclusive classroom.